2021
DOI: 10.1016/j.jcjd.2020.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Do Adult Patients With Type 1 or 2 Diabetes Who Present to the Emergency Department With Hyperglycemia Have Improved Outcomes if They Have Access to Specialized Diabetes Care?

Abstract: Few studies have examined the effect of specialized diabetes care on patients who present to the emergency department for hyperglycemia. Patients followed by specialized diabetes clinics were less likely to have a recurrent emergency visit and require hospitalization for hyperglycemia within 30 days. Future studies involving close endocrinology and emergency medicine collaboration may help reduce recurrent emergency department visits and admissions for hyperglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The 30-day hospitalization rate was 229/24 (10.4%), which was similar to previous studies [10]. There are studies showing that reducing the frequency of recurrent emergency department admissions can be reduced with accessible special diabetes follow-up programs, and it would be bene cial to include all diabetic patients discharged from the emergency department in such family medicine or endocrinology programs [11].…”
Section: Discussionsupporting
confidence: 86%
“…The 30-day hospitalization rate was 229/24 (10.4%), which was similar to previous studies [10]. There are studies showing that reducing the frequency of recurrent emergency department admissions can be reduced with accessible special diabetes follow-up programs, and it would be bene cial to include all diabetic patients discharged from the emergency department in such family medicine or endocrinology programs [11].…”
Section: Discussionsupporting
confidence: 86%
“…A retrospective study in Ontario revealed that patients presenting with hyperglycemia in the emergency department who were then referred to specialized diabetes care had better short-term outcomes. 39 Each encounter should thus be seen as an opportunity to evaluate risk factors of worsening disease and suboptimal disease management and to intervene with appropriate coordinated services where required. This includes opportunities to screen not only for risk factors for kidney disease but also for other related conditions (eg, cardiovascular disease and neuropathy).…”
Section: Pitfalls Along the Journey Of Diabetic Nephropathymentioning
confidence: 99%